Analisis Faktor yang Mempengaruhi Pergeseran Bahasa Daerah Komring dikalangan Generasi Muda - Harahap, Rosminah; Sari, Miranda; S, Sugiarti (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The problem of shifting the use of the Komering regional language among the younger generation is an important highlight in preserving local cultural diversity. The Komering language has an important role as a cultural heritage that maintains the identity of the Komering ethnic community. This phenomenon is caused by modern environmental pressures such as globalization, urbanization, the dominance of the Indonesian language, and social changes that narrow the space for the Komering language. This study aims to analyze the factors causing the shift in the Komering language among the younger generation. The descriptive qualitative research method was used with data collection through in-depth interviews, participatory observations, and documentation studies. The research informants were the younger generation of Komering language speakers in several areas of South Sumatra. The data were analyzed thematically-inductively to reveal the main themes causing the language shift. The results of the study show several main factors causing the shift in the Komering language. First, the dominance of the Indonesian language in the realm of formal education and mass media encourages the younger generation to use Indonesian more in everyday life. Second, the influence of globalization and information technology (social media, television, internet) strengthens exposure to Indonesian and foreign languages. Third, the attitude of the younger generation who considers the Komering language to have a lower social status compared to Indonesian reduces their interest in learning and using the Komering language. Fourth, the family parenting pattern that tends to use Indonesian in communication with children results in Komering children rarely interacting with Komering language from an early age. Fifth, the mobility of the younger generation to big cities limits the use of Komering language in daily interactions.